pH sensitive adsorption of polypeptide/sodium dodecyl sulfate mixtures. - Penfold, J; Tucker, I; Thomas, R; Taylor, D; Zhang, X (2006)
Neutron reflectivity and surface tension have been used to investigate the pH sensitivity of the adsorption of poly-L-lysine hydrobromide and sodium dodecyl sulfate mixtures at the air-solution interface. The surface tension variation with surfactant concentration is complex, and between the critical aggregation concentration and critical micellar concentration there is a marked increase in the surface tension. The neutron reflectivity results show that this is associated with a depletion of the surface of polypeptide/surfactant complexes. The variations in the adsorption and surface tension with pH are attributed to changes in the polypeptide conformation at the interface and in solution.